Pembuatan Game Edukasi Tata Krama untuk Santri TPA Baitussalam Sri Pemandang Berbasis Android - Ermunanda, Eryshta Sevisca; Andriyanto, Sidhiq; Afriansyah, Riki (Jurnal Inovasi Teknologi Terapan, 2024)
In the process of character building of early childhood, it is necessary to instill good attitudes and and be given a place to learn by utilizing technological developments in the learning process. Therefore, it is hoped that educational games can support the enthusiasm of children in learning to understand manners in accordance with Islamic law. Educational games can help educators both teachers and parents in providing manners education This research aims to develop educational games as a learning tool that suits the needs of TPA Baitussalam Sri Pemandang children. The method implemented is the Game Development Life Cycle (GDLC), designed using Unity application and Canva application. In this game there are three learning materials namely Manners, Asmaul Husna, and Prophet Stories. The game runs well and has been tested for functional features by experts. The results of application testing show that the material is in accordance with the source book used in Caberawit learning with a percentage of 95.71%. To calculate User Acceptance Testing, taken from testing to children Caberawit TPA Baitussalam Sri Pemandang get a final score of 85.9%. After doing the UAT calculation, it can be concluded that the manners educational game falls into the "Very Feasible" criteria.